Clinical and virological heterogeneity of hepatitis delta in different regions world‐wide: The Hepatitis Delta International Network (HDIN). (26th October 2017) - Wranke, Anika; Pinheiro Borzacov, Lourdes M.; Parana, Raymundo; Lobato, Cirley; Hamid, Saeed; Ceausu, Emanoil; Dalekos, George N.; Rizzetto, Mario; Turcanu, Adela; Niro, Grazia A.; Lubna, Farheen; Abbas, Minaam; et al.
Abstract: Background & Aims: Chronic hepatitis D (delta) is a major global health burden. Clinical and virological characteristics of patients with hepatitis D virus (HDV) infection and treatment approaches in different regions world‐wide are poorly defined. Methods: The Hepatitis Delta International Network (HDIN) registry was established in 2011 with centres in Europe, Asia, North‐ and South America. Here, we report on clinical/ virological characteristics of the first 1576 patients with ongoing or past HDV infection included in the database until October 2016 and performed a retrospective outcome analysis. The primary aim was to investigate if the region of origin was associated with HDV replication and clinical outcome. Results: The majority of patients was male (n = 979, 62%) and the mean age was 36.7 years (range 1‐79, with 9% of patients younger than 20 years). Most patients were HBeAg‐negative (77%) and HDV‐RNA positive (85%). Cirrhosis was reported in 48.7% of cases which included 13% of patients with previous or ongoing liver decompensation. Hepatocellular carcinoma (HCC) developed in 30 patients (2.5%) and 44 (3.6%) underwent liver transplantation. Regions of origin were independently associated with clinical endpoints and detectability of HDV RNA. Antiviral therapy was administered to 356 patients with different treatment uptakes in different regions. Of these, 264 patients were treated with interferon‐a and 92 were treated with HBV‐Nucs only. Conclusions: The HDIN registry confirms the severity of hepatitis delta but also highlights the heterogeneity of patient characteristics and clinical outcomes in different regions. There is an urgent need for novel treatment options for HDV infection.